Effect of kinesiotape applications on ball velocity and accuracy in amateur soccer and handball - Müller, C.; Brandes, M. (Journal of Human Kinetics, 2015)
Evidence supporting performance enhancing effects of kinesiotape in sports is missing. The aims of this study were to evaluate effects of kinesiotape applications with regard to shooting and throwing performance in 26 amateur soccer and 32 handball players, and to further investigate if these effects were influenced by the players` level of performance. Ball speed as the primary outcome and accuracy of soccer kicks and handball throws were analyzed with and without kinesiotape by means of radar units and video recordings. The application of kinesiotapes significantly increased ball speed in soccer by 1.4 km/h (p=0.047) and accuracy with a lesser distance from the target by -6.9 cm (p=0.039). Ball velocity in handball throws also significantly increased by 1.2 km/h (p=0.013), while accuracy was deteriorated with a greater distance from the target by 3.4 cm (p=0.005). Larger effects with respect to ball speed were found in players with a lower performance level in kicking (1.7 km/h, p=0.028) and throwing (1.8 km/h, p=0.001) compared with higher level soccer and handball players (1.2 km/h, p=0.346 and 0.5 km/h, p=0.511, respectively). In conclusion, the applications of kinesiotape used in this study might have beneficial effects on performance in amateur soccer, but the gain in ball speed in handball is counteracted by a significant deterioration of accuracy. Subgroup analyses indicate that kinesiotape may yield larger effects on ball velocity in athletes with lower kicking and throwing skills.